Temperature Dependence of Surface Polar State of SrTiO3 Ceramics Obtained by Piezoresponse Force Microscopy - Andreeva, N
The existence of polar state on the surface of strontium titanate ceramics was obtained by piezoresponse force microscopy (PFM) in temperature range from 8 to 295 K. This polar state is nonswitchable and relaxes fast at room temperature. This fact is attributed to charge injection from tip, which provoked the formation of oxygen vacancies in subsurface layer. Low temperature dynamics of surface piezoresponse reveals an increasing of PFM contrast at 110–130 K, associated with surface structural phase transition. Temperature dependence of the average level of piezoresponse signal exhibits two peaks due to bulk structural phase transition and coherent quantum state.